Board Characteristics and Earnings Management: Empirical Analysis of UK Listed Manufacturing Companies - WANG, HANYU (2020)
Earnings management has always been a hot issue in the field of accounting research. And previous scholars on the impact of board characteristics on earnings management mainly focused on accrued earnings management. This study selected 93 listed manufacturing companies in the UK from 2014 to 2018 as sample data for regression analysis. It tests whether the proposed hypothesis is reasonable from three aspects: board size, director independence and director gender diversity. Through empirical research, it is found that there is a close relationship between the board characteristics and abnormal accrued profits. The larger the board of directors, the lower the degree of earnings management. The greater the proportion of independent directors in the board of directors, the stronger the constraints on the management's earnings management behavior. However, the correlation between gender diversity of directors and earnings management is not consistent with the hypothesis of this research. The research in this article will help enrich the theoretical research related to accrued earnings management and promote the improvement of the board structure of listed companies. And it is also conducive to the establishment of a reasonable and effective governance mechanism to reduce accrued earnings management. And it helps to promote the healthy and effective operation of the capital market.